Preferencias del consumidor en la ciudad de Riobamba por economía colaborativa: Caso Indrive - Erazo Moscoso, Rita Nicole (2026)
The sharing economy has transformed traditional consumption models, especially in the field of urban transportation. This research analyzes the determinants of Riobamba residents' preferences for using the InDrive app, a collaborative transportation platform. Through a survey of 403 people, and the use of Probit and multinomial Logit econometric models, it is found that prior experience with collaborative services and income level are key factors in the decision to use them. That is, those most likely to use these models are those with experience. Higher incomes reduce the likelihood of use due to having their own transportation. Furthermore, variables such as gender, educational level, and marital status influence the choice of specific platforms. The study highlights the importance of considering both socioeconomic and attitudinal factors to understand consumer behavior in digital and collaborative contexts.